2013
DOI: 10.1097/mbc.0b013e3283566adb
|View full text |Cite
|
Sign up to set email alerts
|

A new D-dimer cutoff in bedridden hospitalized elderly patients

Abstract: Asymptomatic deep vein thrombosis (DVT) and pulmonary embolism are leading causes of morbidity following the hospitalization of elderly people. The diagnosis of DVT is supported by the D-dimer laboratory assay. The concentration of D-dimer increases in patients with DVT, but may be high in other conditions too (i.e. cancer, infections and inflammation). Old age coincides with a physiological increase in D-dimer values, and that is why D-dimer assay in the elderly is characteristically highly sensitive but scar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 19 publications
3
11
0
8
Order By: Relevance
“…A recently published study also evaluated the use of a specific cut‐off level in D‐DU for older patients, but the D‐dimer assay used and the patients included (Auto‐Dimer BIOPOOL DASIT for the diagnosis of asymptomatic DVT in bedridden hospitalized elderly patients) were different from what was used in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study also evaluated the use of a specific cut‐off level in D‐DU for older patients, but the D‐dimer assay used and the patients included (Auto‐Dimer BIOPOOL DASIT for the diagnosis of asymptomatic DVT in bedridden hospitalized elderly patients) were different from what was used in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies presented only isolated terms such as edema, heat, erythema, and pain for describing the clinical picture, without mentioning the word inflammation. (11,13,20,21) Regarding nursing interventions, the non-validated percentage (5.4%) is below the value found in other validation studies of ICNP ® terminology subsets, in which were shown up to 22.6% of non-validated interventions. (4,22,23) This fact may be related to a methodological bias in this study, which refers to the impossibility of the expert performing the evaluation of nursing interventions separately.…”
Section: Resultsmentioning
confidence: 59%
“…The aim of the current study was to explore the reliability of 3 different D-dimer cutoff values: the conventional cutoff (0.5 mg/L), the ROC-derived cutoff value, showing the best specificity while preserving the 100% sensitivity, and the age-adjusted cutoff (age in years  10 mg/L) proposed by Douma et al 21,22 for the diagnosis of asymptomatic VTE in a population of bedridden hospitalized elderly patients in whom the clinical presentation per se wasn't decisive. The current study was carried out on 252 bedridden hospitalized elderly patients with non-high PTP for VTE based on clinical decision rules applying Wells' scoring system ( 2), with exclusion criteria, inclusion criteria, and study design similar to the studies by Granziera et al, 23 Cini et al, 24 Douma et al, 22 Harper et al, 9 and Schouten et al 8 as this is the indicated population for the application of D-dimer tests as opposed to the studies by Lippi et al, 25 Haas et al, 10 Han et al, 26 and Schouten et al 27 who included patients with high PTP for VTE. All patients in our study were subjected to clinical assessment, D-dimer testing, and Doppler examination.…”
Section: Discussionmentioning
confidence: 99%
“…D-Dimer testing in the present study was performed by INNOVANCE D-dimer assay using a CA-1500 Sysmex Siemens analyzer. Other studies [8][9][10][22][23][24]26 assessed different assays on different analyzers: Tinaquant Roche, rapid ELISA Vidas D-dimer bioMérieux, and STA-Liatest D-dimer test, with 5%), and the study reported by Granziera et al 23 had a study population of 199 patients with mean age of 86.3 + 6.7 years, showing 29.1% of patients were admitted due to infection and 12.5% due to the prevalence of DVT, and neither studies showed correlation between any medical grounds for admission and the prevalence of DVT.…”
Section: Discussionmentioning
confidence: 99%